IMMU-20. HEMATOPOIETIC STEM CELLS POTENTIATE EFFICACY OF ADOPTIVE CELL THERAPY AGAINST BRAIN STEM GLIOMA. Issue 2 (22nd June 2018) - Flores, Catherine; Wildes, Tyler; Moore, Ginger; Wummer, Brandon; Mitchell, Duane
Abstract: INTRODUCTION: Adoptive cell therapy has been demonstrably promising in the treatment against cancer, but two major barriers have prevented its application to brain stem gliomas (BSG). First is the penetrance of T cells into BSGs, and the second is that the heterogeneity of brain tumors inevitably results in antigen loss variants when targeting single tumor antigens. We address both limitations with a novel approach of concomitant transfer of hematopoietic stem and progenitor cells (HSC) with adoptive cell therapy in two preclinical models of BSG. METHODS: We use syngeneic models of brain stem glioma, one with wildtype H3.3 and another that harbors the H3.3K27M mutation. Tumor cells were implanted into the brain stems of mice. HSCs were isolated from bone marrow. Tumor-reactive T cells were generated ex vivo against each tumor line by employing dendritic cells pulsed with tumor-RNA. Tumor-reactive T cells were adoptively transferred into tumor bearing mice with or without HSC co-transfer. RESULTS: The efficacy of adoptive cell therapy was significantly increased in cohorts that received HSC co-transfer against both brain stem glioma models. Interestingly, T-cell infiltration into BSGs was only detected in cohorts that received HSC co-transfer. In addition, our observations provide evidence that HSCs co-transferred with IFNγ-secreting anti-tumor T cells differentiate into professional antigen presenting cells as characterized by CD11c, MHC-II, and a lack of MDSC markers. These cells then mount the capacity to capture and cross-prime tumor-derived antigens to both adoptively transferred T cells and host T cells, addressing the diversity of antigens within brain tumors.